Search for New Astronomical Site in Indonesia: III. Astronomical Seeing Condition in West Timor - Budi Dermawan; Putra Mahasena; Taufiq Hidayat; Muhammad Irfan (Jurnal Matematika & Sains, 2010)
Global meteorological study over Indonesia has identified that Nusa Tenggara Timur is a good candidate for an astronomical site. West Timor, in the eastern region of Nusa Tenggara Timur, is subsequently selected to be surveyed both for topographical and sky quality. The latter is studied theoretically in term of transmittance of tropical atmosphere. This work presents in situ measurement undertaken for Kupang (longitude: 123° 34¢ 4² E, latitude: 10° 10¢ 19² S) to derive the seeing values. The same procedure was also performed for Lembang, West Java (longitude: 107° 36¢ 58² E, latitude: 6° 49¢ 33² S) in order to quantitatively compare the proposing site to the established one. Our result shows that Kupang has about 50% better seeing condition than that of Lembang.